Pengaruh Pengangguran Dan Kemiskinan Terhadap Tindakan Kriminal Di Kabupaten Lampung Utara Periode 2012-2021 - Mervita, Eda; Eviatun, Esti; Hasan, Saukani; Hasanuddin, Hasanuddin; Sari, Romida Rifiana (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study was to see how unemployment and poverty affect criminal behavior in Lampung Utara Regency. The data analysis approach used in this research is multiple linear regression, and the type of data used is secondary data obtained from the Central Bureau of Statistics (BPS) and Lampung Utara District Police. The results of this study indicate that (1) In Lampung Utara Regency, unemployment has a negative and small impact on criminal activity. (2) Poverty has a positive but small impact on criminal activity in Lampung Utara Regency Keywords : Crime, Unemployment and Poverty